Pengaruh Customer Experience dan Customer Value Terhadap Revisit Intention di Objek Wisata Taman Lio Baheula Kabupaten Bekasi - Niken Lembayung Basori; Ajat Sudrajat (Peneliti.net, 2022)
The study aims to examine and analyze the effect of Customer Experience and Customer Value on Revisit Intention at Taman Lio Baheula Tourist Attraction, Bekasi Regency. This study primary data with data obtained from distributing questionnaries to visitors visiting Taman Lio Bahula with 100 samples taken using a non-probability sampling method with purposive descriptive analysis and verivicative with SPSS 25 software tools. The result of this study indicate that there is a significant partial effect of Customer Value on Revisit Intention has a greater value of 43,6% while the partial effect of Customer Experience is 31,3%. The simultaneous influence of Customer Experience and Customer Value on Revisit Intention obtained a value of 74,9 and the remaining 25,1% was influence by other variables that not research.